Survival and initial growth of eucalypts species across climatic conditions - Muller da Silva, Paulo Henrique; Lee, David John; Miranda, Aline Cristina; Marino, Celso Luis [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP]; Paula, Rinaldo Cesar de [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2017)
In this study, 19 eucalypt species were evaluated for adaptation under different climatic conditions in Brazil and Uruguary, the majority of these species have no commercial tradition worldwide. Four of the species evaluated were of the Corymbia genus (C. citriodora citriodora, C. citriodora variegata, C. henryi and C. torelliana) and 15 of the Eucalyptus genus from different sections of the Symphyomyrtus subgenus (E. amplifolia, E. argophloia, E. brassiana, E. brookeriana, E. camaldulensis, E. cladocalyx, E. crebra, E. denticulata, E. longirostrata, E. macarthurii, E. major, E. moluccana, E. occidentalis, E. thozetiana and E. urophylla). Eight experiments were set up under different climatic conditions (climates: Am, Aw, Cwa and Cfa), latitude range from 00 degrees 37' to 32o 10'. In Brazil, the trials were set up in Macapa-AP in the Northern Region, Itamarandiba-MG, Paraopeba-MG, Borebi-SP, Itatinga-SP in the Southeastern Region, Tres Lagoas-MS in the Midwest Region, Telemaco Borba-PR in Southern Region and Uruguay near Paysandu City. The treatments were established with rectangular plots of 7 x 7 plants. The adaptability analysis were performed on the survival and initial growth data, using the Harmonic Mean Method of Relative Performance of Genetic Value. The species E. argophloia, E. brookeriana, E. cladocalyx, E. crebra, E. denticulata, E. macarthurii, E. occidentalis and E. thozetiana were poorly adapted, with low survival mainly in tropical conditions (mortality > 50%). The species that had the highest survival in the joint analysis was C. torelliana with survival of 98%. The Macapa trial only had 35% average species survival. In this trial species belonging to Exsertaria section (subgenus Symphyomyrtus)) or the genus Corymbia species from tropical sourcesexhibited good survival, tolerance to leaf spot and growth. The noncommercial eucalypts species that stand out for growth were E. longirostrata, C. henryi and E. major.
Keywords: Eucalyptus; Corymbia; adaptation; biotic and abiotic stresses